Implementation of the Monitoring and Evaluation System (Simonev) in measuring the achievements of development planning programs at the Lampung Province Development Planning Agency - Dwi Puspita, Octa Vallen; Mulyana , Nana; Apandi (Sekolah Tinggi Ilmu Administrasi Lembaga Administrasi Negara, 2024)
The Monitoring and Evaluation System of Development Planning (Simonev) is one of the policies that is part of the e-government system. Therefore, in monitoring and evaluating, it is necessary to be done, one of which is by implementing information technology in the process of monitoring and evaluating the performance of local governments. The results of pre-research observations indicate that program indicators are not yet outcome-oriented. In addition, the lack of unified planning data is also a problem that occurs. This study examines the implementation of the Monitoring and Evaluation System (Simonev) in measuring the achievement of development planning programs at the Regional Development Planning Agency of Lampung Province using Richard E. Matland's theory, which consists of policy accuracy, implementation accuracy, target accuracy, and environmental accuracy, as well as inhibiting factors. Based on the research results using descriptive qualitative methods with data collection techniques, interviews, observations, and documentation, the implementation of Simonev with the theory in question is not optimal based on Richard E. Matland's theory (1995). The measurement of program achievements in Simonev explains that the achievement of programs based on the lack of synchronization between Development programs and performance indicator achievements in planning documents towards evaluation documents